(untitled) (Homoeopathy for All, 2023)
Ageing is a biological process that cannot be reversed. Increasing age in the later part of life also makes a person more susceptible to the extrinsic factors, thus raising the health risks. These health risks become a threat since they encounter the organs undergoing senile changes. The word senile refers to the physical and mental decline, which is associated with the old age. The changes encountered by the body during senility includes problems like stiffening of blood vessels and arteries, diminishing and weakening of bones and muscles reducing flexibility, affections of stability and balance due to improper coordination, constipation due to changes in intestines, diminishing vision or power of hearing, etc. Amongst all, the problem of concern is the cardiovascular diseases.